Interpretation of the climate change in the Carpathian Basin - Loksa, Gábor (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
The Carpathian Basin, in sense of climate, is a transition zone in respect of the continental, the oceanic and the Mediterranean climates. Their different effects result in considerable variability in course of temperature and precipitation, as well as in their geographical distribution. As compared with the basic state, the change, that has started to become more observable in the second half of the twentieth century, still enhances the variability being present, by resulting in appearance of more frequent extreme weather situations. The aim of the paper is to point out the modifications of production site conditions by subsuming the most important properties of modifications in the climate of the Carpathian Basin. Specific data for temporal and quantitative modification in heat and precipitation should be normative to think over the different area uses, crop production and treatment of protected areas and to realize necessary actions. The boundaries of climate change are not known at present, but nature gives some guidelines. Periods with high average temperature (27°C) and burdened with drought has already occurred several times during the latest summers. Additionally, rapid variations in temperature last- ing only for 1 to 2 days but still exceeding 15–20°C have occurred several times during winter and transition seasons. Nature of the present climate change is well characterized by these examples. In addition to the more frequent appearance of temperature extremities, the precipitation course shows considerable change as well. All these facts make the predictability of different weather situations more difficult, and meanwhile the role of short term forecasts is valorized, the exploration of characteristics and stability of mesoclimatic and microclimatic specialties becomes more and more important.